Perkembangan Sektor Basis dan Non Basis di Provinsi Kalimantan Selatan - Dessy Maulina; M. Rusmin Nuryadin (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
Economic growth can be driven by increasing the Gross Regional Domestic Product (GDP) of a region by looking at which sectors are the base or non-base sectors. This study aims to determine the basic and non-base sectors in 13 regencies/cities in South Kalimantan. with a quantitative method using the LQ (Loqation Quetient) index analysis technique using secondary data, namely Regency/City data in South Kalimantan. The results show that the agricultural sector for several regions is still the basis sector. cities in South Kalimantan can be seen from LQ> 1. Then the sector can be interpreted to be superior and if the LQ value < 1 then the sectors in the districts/cities in South Kalimantan are not superior or not dominant.